Powerful practices for high-performing special educators - Kaufman, Roberta Brack; Wandberg, Robert; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2010)
Designed for primary and secondary special educators, this book offers research-based and coordinated instructional strategies that help meet the academic needs of students with disabilities and provides specific examples and scenarios rooted in the realities of special education classrooms or inclusive settings.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Children with disabilities -- Education; Special education teachers; Electronic books